Graphene-Supported Pt-Based Intermetallic as Highly Efficient Catalysts in Fuel Cells - Zheng, L.Z.; Han, K.; Xiong, L.Y.; Zou, Z.J.; Tao, K.; Ye, D. (Asian Journal of Chemistry, 2013)
Graphene-supported Pt and PtxMy (M = Fe, Co and Cu) intermetallic catalysts are prepared by thermal treatment approach and characterized with X-ray diffraction, scanning electron micrographs and rotating disk electrode. Electrocatalytic performance of the prepared materials revealed that they have higher catalytic activity and stability than commercial Pt/C for both the ethanol oxidation reaction and the oxygen reduction reaction in direct alcohol fuel cells. The enhanced electrocatalytic performance of the prepared catalysts is attributed to the Pt alloyed with transition metal (Fe, Co and Cu), which changes both the geometric and electronic structures of Pt in the solution. Therefore, from the electrochemical, morphological and compositional results, it has demonstrated that a better performance of ethanol oxidation reaction and oxygen reduction reaction could be realized at the graphene-supported Pt-based intermetallic catalysts.